1994
DOI: 10.1177/146642409411400304
|View full text |Cite
|
Sign up to set email alerts
|

Use of Obstetric Services in Rural Nigeria

Abstract: The pattern and determinants of maternal service utilization were studied in a rural Nigerian community. The study sample consisted of 488 randomly selected women who had a childbirth or an abortion between May 1987 and September 1989. Although 93% registered for prenatal care in a health care institution, only 51% delivered in a health institution while 49% delivered at home mainly under the care of traditional birth attendants. Factors found to be most consistently associated with the use of health instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 10 publications
6
41
0
1
Order By: Relevance
“…Most studies discussed elaborately on the determinants of utilization of antenatal care or the pattern of use of antenatal care in a specific state, region or locality. Only few studies considered the determinants of the pattern of antenatal care use at the national level (Okafor, 1991;Nwakoby 1994;Osubor et al 2006). This limited the abilities of most studies to give a representative policy and programme recommendation for Nigeria.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Most studies discussed elaborately on the determinants of utilization of antenatal care or the pattern of use of antenatal care in a specific state, region or locality. Only few studies considered the determinants of the pattern of antenatal care use at the national level (Okafor, 1991;Nwakoby 1994;Osubor et al 2006). This limited the abilities of most studies to give a representative policy and programme recommendation for Nigeria.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Because some studies have indicated that women who engaged in less attractive job e.g. farming are less likely to utilize MHCS (Nwakoby, 1994;Addai, 2000).…”
Section: Employmentmentioning
confidence: 99%
“…Most of the population-based studies were small-scale research, focusing on a handful of communities, usually small-sized rural communities [27][28][29]. Their geographic scope limits the applicability of their result on a large scale, particularly considering the complex multi-ethnic setting of Nigeria.…”
Section: Introductionmentioning
confidence: 99%